Conservation, biodiversity and world heritage reef advisory committee 17th meeting 2005 - (:unkn) unknown (Great Barrier Reef Marine Park Authority, 2005)
A summary document is prepared after each meeting of the Reef Advisory Committee (RAC) to inform other advisory committees serving the Authority, and persons generally (including the public), of the business of the RAC. The document forms part of the records of the meeting and so its content is limited to matters raised in the meeting, and, where necessary, background details given to the meeting. Any inquiries should be referred to the Great Barrier Reef Marine Park Authority’s (GBRMPA) RAC Secretariat, or to the appropriate Member.
Keywords: Biodiversity; Conservation; Environmental management; Managing Multiple Use; Information Publication Scheme; World heritage; Leading environmental practice; Reef-wide